ENHANCING COLD CHAIN RESILIENCE: A DUAL FOCUSON RISK MANAGEMENTWITH SUSTAINABLE SOLUTIONS (UKLO Proceedings, 2025)
The cold chain logistics faces challenges maintaining product integrity while achieving sustainability goals. This article explores the relationship between risk management practices and cold chains sustainability, identifying how sustainable practices such as energy-efficient refrigeration, renewable energy sources, advanced digital monitoring, enhance resilience against cold chain risks. Problems addressed include primary cold chain risks identification, like spoilage, regulatory compliance, cost volatility, and understanding how sustainable practices mitigate these issues while supporting operational continuity. The synergy between risk mitigation strategies and sustainability measures, contribute to resilient, environmentally friendly cold chain systems. Reviewed studies on sustainable cold chain logistics, risk management frameworks, relevant technologies like IoT, blockchain, and data analytics and qualitative analysis of world-wide cutting-edge implementations case studies, address sustainable resilience enabling key factors. Sustainable practices, such as energy-efficient storage, reducing temperature excursions, smart packaging, minimizing waste, lowering carbon emissions, reduce environmental and logistical impact. Integrating sustainability as core strategy in cold chain logistics, and research on new green technologies’ role advance these objectives. Moreover, companies implementing green technologies and robust risk management strategies achieve both sustainability targets and improved cold chain reliability. This dual focus on risk and cold chains sustainability offers a blueprint for resilient and environmentally conscious logistics operations.